PENGARUH PENERAPAN METODE STAD DENGAN MENGGUNAKAN LABORATORIUM VIRTUAL TERHADAP HASIL BELAJAR KIMIA SISWA - vivi rayanti; Elvi Yenti (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThis research is prompted by students’ low learning outcomes. One of the ways that can be performed to increase students’ learning outcomes is Student Teams Achievement Division (STAD) learning method by using virtual laboratory. This research is aimed at looking at the effect of STAD learning method by using virtual laboratory toward students’ learning outcomes in Redox Reaction material of grade 10 students at State Senior High School 1 Mandau. This research is a quasi-experiment research by using Pretest-Posttest Control Group Design with two sample classes: Class X 3 as experiment research and Class X 4 as control class. In this research, the meeting was conducted for four times. The techniques of collecting the data in this research are Homogeneity test as initial data, Pretest and Posttest as final data, Interview, and Documentation. Initial and final data are analyzed by using t-test. This research shows that there are some differences on students’ learning outcomes between experiment class and control class. Final data analysis generates the value of tcounting = 2.8904 and ttable = 1.9983 that shows tcounting > ttable. As Ho is rejected, it can be concluded that there is an effect of applying STAD learning method by using virtual laboratory toward students’ learning outcomes which is as much as 11.70%.Keywords: STAD, virtual laboratory, redox reaction